Pengaruh Struktur Modal dan Efisiensi Operasional terhadap Profitabilitas Bank Swasta Nasional yang Terdaftar di Bursa Efek Indonesia Periode 2020–2024 - Eka Nur Wijayanti; Ita Rahmawati (MAMEN: Jurnal Manajemen, 2026)
This study aims to examine the effect of capital structure and operational efficiency on the profitability of national private banks listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Capital structure is proxied by the Capital Adequacy Ratio (CAR), while operational efficiency is measured using the Operating Expenses to Operating Income (BOPO) ratio. Bank profitability is represented by Return on Assets (ROA). This research adopts a quantitative approach employing multiple linear regression analysis. The data used are secondary data obtained from the annual financial statements of five national private banks selected through purposive sampling. The analysis procedures include descriptive statistics, classical assumption tests, partial hypothesis testing, simultaneous testing, and coefficient of determination analysis. The results indicate that CAR has a positive but insignificant effect on ROA, suggesting that the level of capital adequacy has not been optimally utilized to directly enhance bank profitability. In contrast, BOPO has a negative and significant effect on ROA, indicating that higher operating expenses tend to reduce profitability. Simultaneously, CAR and BOPO significantly affect ROA with a coefficient of determination of 0.714. These findings highlight that operational efficiency plays a more dominant role than capital structure in determining the profitability of national private banks during the study period.